Perfil psicológico y conductual de una muestra de Parejas heterosexuales Mexicanas - Sánchez-Aragón, Rozzana; Díaz-Loving, Rolando (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Couple relationships offer the perfect setting for individuals to express their capabilities, affection, beliefs, deficiencies, virtues and defects. In these relations, both the good and the dark side of human essence transcend. Taking into account both sides, 154 Mexican participants indicated their coping, love and communication styles in conjunction with the acceptable, insufficient and offensive behaviors prevalent in their daily couple´s interaction. The psychological and behavioral representation obtained from a second order factor analysis includes dimensions of Negative Interaction, Fair and Positive Interaction, Instability and Abnegation, Friendship and Functionality, Erotism and Jealous Love with reliability coefficients over .80. Gender difference of these reliable factors and their implications for daily interaction are presented and discussed.